2023
DOI: 10.3390/healthcare11101497
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Cerebrolysin after Ischemic Stroke: Secondary Analysis of the CARS Study

Abstract: The cost-effectiveness of Cerebrolysin as an add-on therapy for moderate–severe acute ischemic stroke is a topic that remains understudied. This study aims to address this gap by performing a comprehensive cost-utility analysis using both deterministic and probabilistic methods from a payer perspective and within the Romanian inpatient care setting. Quality-adjusted life years (QALYs) were calculated using partial individual patient data from the 2016 Cerebrolysin and Recovery After Stroke (CARS) trial, utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…After layer-by-layer screening according to the inclusion and exclusion criteria, a final set of 14 articles was included, including 8 SR or meta-analysis [15–22] and 6 pharmacoeconomic studies. [25–30] No HTA report was retrieved. The literature screening process and results are provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After layer-by-layer screening according to the inclusion and exclusion criteria, a final set of 14 articles was included, including 8 SR or meta-analysis [15–22] and 6 pharmacoeconomic studies. [25–30] No HTA report was retrieved. The literature screening process and results are provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six pharmacoeconomic evaluations of Cerebrolysin intervention were included, all adopted cost-effectiveness analysis. The study by Strilciuc et al [ 30 ] demonstrated that, at a cost-effectiveness threshold of 50,000 euros, the addition of Cerebrolysin treatment showed favorable cost-effectiveness for moderate to severe AIS. The research findings from Men et al [ 28 ] and He et al [ 29 ] both support that, compared to conventional treatment alone, the incremental cost-effectiveness ratio (△C/△E) is lower with the combination of Cerebrolysin injection.…”
Section: Resultsmentioning
confidence: 99%